Monocyte subset distribution in myeloproliferative and myelodysplastic/myeloproliferative neoplasms with monocytosis. (January 2022) - Sorigue, Marc; Arenillas, Leonor; Xicoy, Blanca; Andrade-Campos, Marcio; Navarro, Jose-Tomas; Ferrer, Ana; Zamora, Lurdes; Calvo, Xavier
Highlights: It is unknown whether %MO1 can distinguish between CMML and other myeloproliferative malignancies. We analyzed the %MO1 in 24 patients with MPN or non-CMML MDS/MPN and monocytosis. 21 patients (87.5 %) had MO1 ≤ 94 %. The %MO1 discriminates well between CMML and other MPN or non-CMML MDS/MPN and monocytosis.